Penguatan Etika Islam dalam Birokrasi di Banten - Feramahdalena, Elsa; Rosidin, Angga; Wahyudi, Heru; Maulana, Jaka (ANTASENA: Governance and Innovation Journal, 2025)
Islamic ethics reflect human behavior grounded in the values and teachings of Islam within social life—whether in the family, community, nation, or state. In the context of Indonesia's bureaucracy, applying Islamic teachings is essential to shaping bureaucrats who are not only competent but also possess strong moral integrity. High-quality public service depends not only on the technical abilities of bureaucrats but also on the ethical values that guide their conduct. Therefore, integrating Islamic values into the bureaucratic system is a necessary step toward improving the quality of governance. This study aims to develop bureaucrats with Islamic ethical character by referring to the primary sources of Islamic teachings, namely the Qur’an and Hadith. The method used in this research is a literature review, analyzing various references related to Islamic ethics and bureaucratic behavior. The findings reveal that ethics play a critical role in the success of bureaucratic functions. By internalizing Islamic values, bureaucrats can gain a religious understanding that guides them in distinguishing right from wrong and avoiding unethical behavior. The formation of Islamic ethics within the bureaucracy requires instilling noble traits such as honesty, trustworthiness, fairness, and responsibility. These values, deeply rooted in Islamic teachings, serve as a foundation for shaping ethical public officials. By integrating Islamic ethics into public administration, the behavior of bureaucrats can be directed toward greater integrity and accountability, thereby minimizing the potential for maladministration and contributing to a more effective and transparent government system.